PKM Panti Asuhan Bayi dan Balita “ Fajar Harapan” Pekanbaru - Made Devi Wedayanti; Novia Nazirun (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
The Baby and Toddler Orphanage " Fajar Harapan " is located at Jalan Mustafa Yatim No.12 Pekanbaru, Riau and is chaired by Mr.H. Yazid Bakhri. Currently this orphanage accommodates 77 children consisting of 11 babies, 15 toddlers, 21 people in elementary school, 30 people in high school and junior high school with 6 caregivers. This orphanage has various problems including: First, it only relies on donors to meet financial needs such as the community and the government. Second, the level of health awareness in the orphanage is still lacking, such as the number of children experiencing scabies, lice, itching and tinea versicolor. Third, there is still a lack of bed facilities so that the orphans only sleep on thin carpets (mats). PKM is carried out in several stages including: training, implementation and evaluation. The solutions offered by this PKM program include three things: counseling, mentoring, treatment and providing facilities